2021
DOI: 10.1016/j.asmr.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Superior Capsular Reconstruction for Massive, Irreparable Rotator Cuff Tears: A Systematic Review Comparing Acellular Dermal Allograft and Autograft Fascia Lata

Abstract: Purpose To investigate clinical outcomes after superior capsular reconstruction (SCR) for the treatment of massive and/or irreparable rotator cuff tears treated with either allograft or autograft. Methods Using the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines, in April 2020 a systematic review was performed using PubMed, MEDLINE, EMBASE, and Cochrane databases. Clinical studies were assessed for patient-reported outcomes and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“… 26 Systematic reviews could not compare clinical outcomes between different types of grafts and highlighted the heterogeneity among the studies. 9 , 22 , 30 , 42 , 45 , 51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Systematic reviews could not compare clinical outcomes between different types of grafts and highlighted the heterogeneity among the studies. 9 , 22 , 30 , 42 , 45 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…26 Systematic reviews could not compare clinical outcomes between different types of grafts and highlighted the heterogeneity among the studies. 9,22,30,42,45,51 The good results of ASCR that uses AFL come with a price: the additional harvesting procedure and the resultant residual symptoms. According to the current study, 95% of the patients considered the price to be fair and would be willing to undergo the procedure again.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, use of fascia lata autograft comes with increased risks of donor site morbidity and increased operation time. Dermal allografts are also popular 10,11,12 in SCR; however, they result in a thinner graft (3-4 mm) and they costs more.…”
Section: Discussionmentioning
confidence: 99%
“…SCR has been increasingly investigated and reported in recent years. In a systematic review, graft tears in the dermal allograft and the autograft fascia lata were reported to be 13.9% overall [25]. A wide range of failure rates has been reported, depending on the type of graft: 5%-32% for the fascia lata autograft and 20%-70% for the human dermal allograft.…”
Section: Discussionmentioning
confidence: 99%